The effect of effervescent acanthus ilicifolius l. extract on antifungal properties and flexural strength acrylic - Widyasri Prananingrum; Fitria Rahmitasari; Dwi Andriani; Arifzan Razak (Odonto : Dental Journal, 2022)
Background: Acanthus ilicifolius L. has antifungal potential and makes it possible to be a candidate for denture cleanser. This study aims to evaluate the effect of effervescent Acanthus ilicifolius L. extract on antifungal properties and flexural strength acrylic after immersion for three duration times.Method: Extracts were made by maceration method with ethanol. For the antifungal test, effervescent Acanthus ilicifolius L extract was prepared by combining the Acanthus ilicifolius L extract 4% and sodium perborate with two ratios, 1:7 and 1:14. The microdilution method was carried out. Effervescent Acanthus ilicifolius L extract 4% with ratio 1:7 was prepared for the flexural strength test. The fifty-four heat-cured acrylic resin (20x10x2.5mm) were fabricated and divided into 3 groups. Group 1 was immersed in aquadest (control); Group 2 was immersed in sodium perborate; Group 3 was immersed in effervescent Acanthous ilicifolius L. extract. Each group was immersed for 15 min, 8, and 56 hours (n=6). The flexural strength test was performed using Universal Testing Machine.Result: Effervescent Acanthus ilicifolius L. extract exhibited antifungal activity which increased in an effervescent Acanthus ilicifolius L extract-dependent manner significantly (0.57 to 0.50 OD). There were no significant differences between sodium perborate, effervescent_AI1 (1:7) and effervescent_AI2 (1:14). The flexural strength was found to be within the range of 66.1 - 68.3 MPa. There were no significant differences between groups (p < 0.05).Conclusion: Effervescent Acanthus ilicifolius L extract with the ratios 1:7 had a good antifungal effect and appropriate flexural strength after immersion for 15 min, 8, and 56 hours.